Marine Water Quality Mapping in Rupat Strait with Modelling Hydrodynamics - Chandra M Aulia; Syahril Nedi; Elizal Elizal (Tropical Marine Enviromental Sciences, 2024)
This research aims to analyze water quality and determine the status of quality standards in the waters of Rupat Strait. The method used in the study is comparative descriptive analysis and literature analysis. Hydrodynamic and water quality models with MIKE 21 Hydrodynamics and ECO Lab modules were used to examine the distribution of water quality parameters in the waters of Rupat Strait. The results showed that the waters of the Rupat Strait have a depth between 2-15 m with a velocity of 0.15-0.3 m/s. DO concentration has an interval of 5-6 mg/L, then BOD concentration has an interval of 0.8-2.4 mg/L, salinity has an interval of 17- 27‰, and temperature has an interval of 26-310C. Water quality in Rupat Strait is still within the quality standards. The pollution index calculation in Rupat Strait obtained values between 1<IP<5, indicating that Rupat Strait is still classified as lightly polluted